A MODEL FOR FOSTERING A SOCIALLY ACTIVE STANCE IN FUTURE PHYSICAL EDUCATION TEACHERS IN HIGHER PEDAGOGICAL EDUCATION (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
Special programs specifically aimed at developing a socially active stance in students are not currently available in higher education institutions that prepare future physical education teachers. At the same time, the societal need for physical-education specialists who possess an active social position has long been recognized [68]. In response to this need, we have designed a model for fostering a socially active stance in students training to become physical education teachers within the context of Chirchik State Pedagogical University; the model is shown in Figure 2.